Inovasi Frozen Vegetable Sebagai Produk Andalan Oleh-oleh Khas Desa Wisata Belirang - Hilda Meisya Arif; Hesti Nur’aini; Eko Sumartono; Methatias Ayu; Andwini Prasetya (Universitas Dehasen Bengkulu, 2023)
Vegetables are still generally traded in fresh form. Unlike the case with fruits, processed vegetable products are almost said to have no well-established processed products in Indonesia. The technology applied is fermentent vegetables such as salted vegetables and drying which are still limited in nature. Frozen vegetables are one way of preserving agricultural products in the form of vegetables using low temperatures. Freezing can kill some types of microbes which is detrimental sometimes even up to more than 90%. Freezing treatment can be carried out on some mixed products of several vegetables that are ready for use. Frozen Food Technology can be a solution in extending the shelf life and durability of a product. The advantage of food freezing techniques is that food quality such as nutritional value and organoleptic properties are maintained. The bliter seberang village area is planted with various types of agricultural crops such as corn, tomatoes, chilies, celery leaves, carrots and others (Profile of Belitar Seberang Village, 2021). As for vegetables by residents, they are sold immediately after harvesting, but if the vegetables are not sold, they will be consumed by themselves or thrown away if they start to rot. Due to the limited knowledge of the community until now, no one has tried to make vegetables in frozen form or Frozen Vegetable, so the taste still requires a touch of processing and packaging technology that can add to its selling value and maintain its durability so that it is not easily damaged. Frozen vegetables that are packaged well are expected to be more durable and practical to carry around and can become typical souvenirs of Wsata Belitung Village. It is hoped by the service team that the community who have received counseling and training on